A participação em instituições descentralizadas na cidade de João Pessoa: o orçamento democrático e o conselho de saúde - Férriz, Adriana Freire Pereira (2012)
The thesis examines the participation of the population of the communities involved in decentralized institutions of the municipal management of Joao Pessoa, which were implemented in the Federal Constitution of 1988, having as main focus, the Democratic budget and the Board of Health started from is assumed that in the last three decades, Brazilian society has been experiencing significant changes regarding the management of public resources marked by the implementation of a new form of government conduct that seeks a transition from a centralized to a more decentralized model, marked for greater direct participation of the population and decision making. In this sense, the main objectives of this study were: to analyze the distributional impact of citizen participation in these decentralized institutions, develop a typology of each institution decentralized participatory (history, composition, legislation, implementation capacity and effectiveness) and the profiles of participants from each institution participatory. To this end, the stage of data collection, desk research was prioritized by understanding that the documents may reveal the potential of these institutions. Thus, two types of documents were reviewed: those produced on the city of Joao Pessoa and produced by the Democratic budget and the City Council Health Treatment of the documents was made possible through the assessment undertaken from the definition of six analytical categories: degree of institutionalization, institutional form and nature, participation, representation, deliberation and distributional impact. The research provided sufficient evidence to affirm that there is a relationship, sometimes revealing similarities, sometimes differences between the Democratic budget and the Board of Health, revealed through the patterns of discussion, the form of organization, visibility and range of each institution, the methodology adopted, the legislation that guides and nature of each. However, the relationship between the two institutions did not consolidate until there is, between them, an articulation of public policies permanent, despite parity discuss themes and objectives. Therefore, it is believed that people's participation in the Democratic budget and the Board of Health is likely to modify the relationship between society and government, with a strong tendency for the growth of civic consciousness, which is expressed also in a very early. In the same vein, you can not even see, so strong, very significant changes in the conditions of life due to the direct care of the demands posed by participation in the OD and CMS, although the process is recognized as important by the directors of both institutions.